Smart Drain Concrete Concrete-Based Smart Drainage System Innovation - Mukhtar, Affidah Mardziah; Kadir, Siti Hawa; Nor, Nor Hayati Mat; Nawawi, Nor Afiqah Mohd (Tropical Scientific Journal, 2026)
Objective: This study presents the development and evaluation of Smart Drain Concrete, an innovative drainage system designed to reduce urban flash floods and promote sustainable water management. The objectives of this study were to design a modular U-shaped precast drain, evaluate the water absorption performance, evaluate the compressive strength of the microbiological concrete mix, determine the flow rate through the ECO2GC Darin Cover and build a prototype for urban applications. Research Method: The system was constructed using Grade 40 concrete enhanced with 3% Bacillus subtilis to improve durability and self-healing properties, combined with the Eco2GC drain cover, natural filtration layer and porous pipe. Laboratory testing was carried out according to BS EN 12390-7:2019 standards, with water absorption assessed by oven drying and immersion methods, BS EN 12390-3:2019 for compressive strength tested using cube specimens under controlled load and BS EN 12390-8:2012 for Determination of Flow Rate through Concrete. Findings: The results of the study showed that the microbiological concrete achieved a compressive strength of 45 MPa at day 28, a permeability of 0.03 mm, demonstrating a balance between structural strength and hydraulic function. The porosity test value with a flow rate value of 0.199 liters/second showed that the porous system maintained hydraulic efficiency. A 1:4 scale prototype test confirmed the system’s ability to control absorption, filter impurities and enhance groundwater reabsorption. The originality of this study lies in the integration of microbiological self-healing technology with sustainable drainage design, enabling dual structural and ecological performance. Findings: Furthermore, collaboration with industry partner VCI IBS Sdn. Bhd. highlights its commercialization potential through pilot-scale testing, IoT-based monitoring and sustainability certification. Overall, Smart Drain Concrete shows high potential as a scalable, cost-effective and environmentally friendly drainage solution for housing, green building and smart city applications, in line with global sustainability goals (SDGs 6, 9, 11, 12 and 13)